The Influence Of Psychological Factors And Investor Personality On Investment Performance With The Mediation Of Financial Decision-Making - Chairul Suhendra; Anisaul Hasanah; Andi Primafira Bumandava Eka (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
The study explores the intricate relationships among psychological factors, investor personality, financial decision-making, and investment performance within the context of PT Agiaga Jaya Perkasa. Utilizing a sample of 50 individuals, the research employs a robust methodology, including random sampling and Structural Equation Modeling with the Partial Least Squares approach. The direct test results reveal significant influences of psychological factors and investment performance on financial decision-making, while the indirect test results highlight the mediation role of financial decision-making in the relationship between psychological factors and investment performance. Notably, the study finds a nuanced interaction between investment performance and financial decision-making. These findings contribute valuable insights for PT Agiaga Jaya Perkasa, underscoring the importance of managing psychological aspects in decision-making processes and refining investment strategies for optimal financial outcomes. The study enriches the understanding of the complex dynamics at play in corporate investment settings, offering practical implications for enhancing overall financial success.